Determination of thermo-mechanical variables during plain strain compression testing - Buchanan, James McCallum (Centre for Materials Engineering, 2023)
Plane strain compression (PSC) resting is a method used to simulate the deformation condition of industrial rolling, namely that of plane strain, and is used extensively to describe the influence of deformation variables, being strain, strain rate and temperature, on microstructural evolution. However, the strain and strain rate within deformed PSC specimens is not homogeneous and for high strain rate deformation (tsec·1) localized adiabatic heating may occur. Nominal values of strain and strain rate do not describe the mechanical deformation variables in a particular volume of the PSC spearmen. Therefore, for analytical microstructural models to have better predictive value, the determination of the thermo-mechanical variables during PSC testing is required. The strain and strain rate distribution during PSC resting of aluminium is investigated using visioplastic experiments and the Finite Element Method (FEM). Visioplastic analysis allows the reaJ state of deformation to be investigated, which is then used to verify and validate the FEM predicrion. The study showed that gTapbite lubrication breakdown occurs progressively above 300 °C, leading to a change in strain and strain rare distribution because of an increased coef6cient of friction as the test temperature is increased. Lubrication breakdown has been characterised using a Coulomb friction model for PSC testing temperatures between 25 and 440 °C, which when incorporated into a FEM model for a specific deformation temperature more accurately predicts the real state of deformation within the PSC specimen. The temperature distribution during PSC testing has been investigated using the FEM, microstructural investigation and microhardness analysis. With the strain and strain rate having being characterised. the temperature distribution has been investigated by considering the stored energy variation attributed to partially recrystallized microstructures and rnicrohardness distributions for a particular combination of strain, strain rate and temperature. The study showed that the temperature distribution before and during PSC testing is not homogeneous. The inhomogeneous temperature distribution is attributed to the electrical resistance heating method employed co heat the PSC specimen. The inhomogeneity of temperature distribution was nor characterised as 1r was beyond the scope of the study.